The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.physio.2007.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Reflection in an intermediate care team

Abstract: Objectives Reflection has been cited as an effective method of providing evidence of professional development, learning and continued competence. Reflection in teams is thought to develop trust within the team and greater understanding of other team members' roles and responsibilities. The aim of this qualitative study was to describe the experiences and perceptions of reflection by members of an intermediate care team. Design Phenomenological design, consisting of individual semi-structured audiotaped intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…When the mechanism was absent, teams did not formally review their performance or the outcome of specific situations together. Reflection sometimes still occurred, but within uniprofessional or other small groups or in an ad hoc, informal way (Sutton & Dalley, 2008).…”
Section: Critical Reflectionmentioning
confidence: 99%
“…When the mechanism was absent, teams did not formally review their performance or the outcome of specific situations together. Reflection sometimes still occurred, but within uniprofessional or other small groups or in an ad hoc, informal way (Sutton & Dalley, 2008).…”
Section: Critical Reflectionmentioning
confidence: 99%
“…As indicated above, one potential moderator of the relationship between group reflection and learning outcomes is the content of the reflection itself (Sutton & Dalley, 2008). Many of the earlier studies of group reflection (or group reflexivity; West, 1996) involve case studies in which group reflection is self-reported after the fact, so the actual content of the reflection cannot be observed (Moreland & McMinn, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Systematic consideration should also be given to the questions used to elicit individual and group reflections. Although most reflection interventions ask individuals to think about strategies for improving their performance (e.g., Gurtner et al, 2007), little research has considered whether the types of questions are likely to yield different forms of reflection and whether different types of reflection (e.g., reflection on task strategies versus reflecting on the quality of the group’s interactions) are more or less valuable in facilitating performance (Moreland & McMinn, 2010; Sutton & Dalley, 2008). It may be that more specific, concrete questions (“What were two specific strategies that you could use to improve in the future?”) are more useful than open-ended, general questions (e.g., “What are some suggestions for how you could improve task performance in the future?”).…”
Section: Directions For Future Researchmentioning
confidence: 99%